Private Education in China Achievement and Challenge - Zhou, Haitao; Liu, Qiang; Tian, Jing.; Li, Qian.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2018)
This book takes an in-depth look at the development of the private education sector in modern China. Readers will find valuable data and materials never before presented in such an accessible and transparent way, together with analyses of the major changes and challenges in the course of this development. The book is organized both chronologically and by topic: it employs a past-present-future order that unites the general arrangement; at the same time, each specific subject is approached historically, not only to show the origins of the problem, but also to link it with the historical-comparative context, in which the evaluation of alternative policy choices become highly viable. Further, the book provides a pioneering account of current problems, adopting a fresh perspective to address the most important aspects of Chinese private education reform. The elaboration on topics concerning private school assets, property rights, legal personality, school operators$1 (Bentrepreneurship, benefits and investment returns, school autonomy, and the development of teachers and students, is both empirically rich and highly insightful. The book$1 (Bs content is chiefly derived from years of fieldwork in private schools and from extensive interviews with hundreds of policy makers, school operators, managers, teachers and students. Since these people are self-conscious about themselves as the actors in and witnesses to the development of Chinese private education over the past three decades, the book places great emphasis on neutrality, allowing the private education landscape to unfold in the context of the privatization of the socialist system after 1978. The book offers an essential guide for anyone who wishes to understand the transformation of Chinese education. It is highly recommendable as a detailed introduction to Chinese education, or as a resource for comparative research on private education from an international perspective.s
Chapter 1 Private Education and the Tale of Two Sectors -- Chapter 2 Private Education Development at a Glance Since 2003 -- Chapter 3 The Legal Person's Classification Registration and the Ownership of Property in Chinese Private Education -- Chapter 4 The Ownership of Property Rights of Chinese Private Institutions -- Chapter 5 Chinese Private Education Public Financial Assistance -- Chapter 6 Governance System of Private Schools -- Chapter 7 Rights and Interests Guarantee of Private School Teachers -- Chapter 8 New Reality: Supporting and Regulating Nongovernmental Forces in Education Sectors.
Keywords: Administration, Organization and Leadership; Educational Policy and Politics; Teaching and Teacher Education; Learning & Instruction